CSL controls telomere maintenance and genome stability in human dermal fibroblasts - Giulia Bottoni (Nature Portfolio, 2019)
Conversion of dermal fibroblasts into Cancer Associated Fibroblasts (CAFs) can play an important role in keratinocyte tumour development. Here the authors reveal that CSL plays a role in maintenance of telomeres and genomic integrity in both dermal fibroblasts and CAFs.